Islamic Education Politics Ambiguity of Policy Intepretation in Islamic Religious College: between Negotiation and Institutional Authority - Muhammad Miftah (LPPM IAIN Kudus, 2019)
The superior development priority of Human Resources (HR) is the answer to the twisted development of the Industrial Revolution Era 4.0 which is currently booming. Increasing the competitiveness of the Indonesian people through education is a logical and philosophical argument; which the demographic bonus that Indonesia has in 2020 more than 67% of the Indonesian population is in productive ages. Islamic Religious College is one of the locomotives that is believed to be able to deliver its demographic bonus in accordance with the Strategic Plan owned by the Indonesian. This opportunity has also been captured by the education world with the issuance of the Indonesian Qualification Framework (Kerangka Kualifikasi Nasional Indonesia, KKNI) policy and strategic policies issued by the Ministry of Research, Technology, and Higher Education (Kementerian Riset, Teknologi, dan Pendidikan Tinggi) and the Ministry of Religion (Kementerian Agama) in welcoming the rapid development. The policy product resulted by the Ministry of Research, Technology, and Higher Education and the Ministry of Religion at the upstream level has the same goal, but at the grassroots downstream level the policy implementation in each of Islamic Higher Education (Perguruan Tinggi Keagamaan Islam, PTKI) is very dynamic and sometimes also contradictory to the policies of this institution. The focus of this research is to examine the contradictory realities in implementing interrelated policies in various Islamic Religious Colleges using a qualitative approach. The findings of this research can be concluded that dynamics, contradictions in the policies implementation in various PTKIs due to social conditions, campus politics, academic culture and the authority leader who lead a university, become a trigger for multiple interpretations of a policy product.